2015
DOI: 10.18632/oncotarget.5582
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of CD19 chimeric antigen receptor-modified T cells for treatment of B cell malignancies in phase I clinical trials: a meta-analysis

Abstract: Chimeric antigen receptor (CAR) modified T cells targeted CD19 showed promising clinical outcomes in treatment of B cell malignances such as chronic lymphocytic leukemia (CLL), acute lymphoblastic leukemia (ALL) and other indolent lymphomas. However, the clinical benefit varies tremendously among different trials. This meta-analysis investigated the efficacy (response rates and survival time) of CD19-CAR T cells in refractory B cell malignances in Phase I clinical trials. We searched publications between 1991 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
86
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 109 publications
(93 citation statements)
references
References 43 publications
7
86
0
Order By: Relevance
“…The development of highly sensitive MRD techniques standardized for all patients, genetic profiling and identification of other predicting factors are required for better-individualized treatments. Emerging therapies like bi-specific antibodies 23,24 and CAR T cells 25,26 will profoundly modify the landscape of resistant ALLs, but these targeted therapies are still lacking for childhood AML.…”
Section: Discussionmentioning
confidence: 99%
“…The development of highly sensitive MRD techniques standardized for all patients, genetic profiling and identification of other predicting factors are required for better-individualized treatments. Emerging therapies like bi-specific antibodies 23,24 and CAR T cells 25,26 will profoundly modify the landscape of resistant ALLs, but these targeted therapies are still lacking for childhood AML.…”
Section: Discussionmentioning
confidence: 99%
“…CAR T cells with 4-1BB costimulation persisted for more than 6 months in the blood of most patients, whereas CD28 CAR T cells were mostly undetectable beyond 3 months [23]. CD28 CAR T cells show a reprogramming toward CD45RO + CCR7 − effector memory maturation while 4-1BB CAR T cells predominantly show a CD45RO + CCR7…”
Section: The Prototype Carmentioning
confidence: 97%
“…However, a recent meta-analysis of CD19 CAR T cell trials confirmed lymphodepletion and CAR T cell dose as key factors for successful treatment, while IL-2 co-administration is not recommended [23]. Most patients with 4-1BB-CD3ζ CAR T cell therapy did not receive further treatment; patients treated with CD28-CD3ζ CAR T cells frequently underwent subsequent allogeneic stem cell transplantation; the clinical decision is partly based on the observation that 4-1BB-CD3ζ CAR T cells persist over years while CD28-CD3ζ CAR T cells persist only for a few months.…”
Section: Current Efforts Are Aiming At Sustaining Engraftment and Impmentioning
confidence: 99%
“…The median interval of PFS was 7.0 months. Higher numbers of infused CAR-T cells and lymphodepletion were associated with a better prognosis [36].…”
Section: Single Car-t Cells For Refractory/relapsed All Treatment Of mentioning
confidence: 99%
“…Altogether, approximately 40-90% of patients with refractory/relapsed ALL can reach complete molecular or cellular remission through treatment with CAR-T cells; however, because CAR-T cells survived in the body for only a short time, some of the patients relapsed quickly, which may be related to the different in the costimulatory molecular or vectors used, or variation in the disease burden across treated individuals [36,37] (Table 1). Thus, other treatments should be performed to improve outcomes in the treatment of refractory/relapsed ALL.…”
Section: Single Car-t Cells For Refractory/relapsed All Treatment Of mentioning
confidence: 99%